Alternative Splicing and Transcription Elongation in Plants - Godoy Herz, Micaela A.; Kornblihtt, Alberto R. (Frontiers in Plant Science, 2019)
Alternative splicing and transcription elongation by RNA polymerase II (RNAPII) are two processes which are tightly connected. Splicing is a co-transcriptional process, and different experimental approaches show that splicing is coupled to transcription in Drosophila, yeast and mammals. However, little is known about coupling of transcription and alternative splicing in plants. The kinetic coupling explains how changes in RNAPII elongation rate influence alternative splicing choices. Recent work in Arabidopsis shows that expression of a dominant negative transcription elongation factor, TFIIS, enhances exon inclusion. Furthermore, the Arabidopsis transcription elongation complex has been recently described, providing new information about elongation factors that interact with elongating RNAPII. Light regulates alternative splicing in plants through a chloroplast retrograde signaling. We have recently shown that light promotes RNAPII elongation in the affected genes, while in darkness elongation is lower. These changes in transcription are consistent with elongation causing the observed changes in alternative splicing. Altogether, these findings provide evidence that coupling between transcription and alternative splicing is an important layer of gene expression regulation in plants.